What Happened to the Women? An Analysis and Discussion of Early Women Adult Educators - Susan Imel; Gretchen T. Cersch Professor Emerita (Adult Education Research Conference, 2008)
This analysis of early women contributors in adult education focuses on the period between the founding of the American Association for Adult Education (AAAE) in 1926 and 1950, when AAAE was replaced by the Adult Education Association of the USA. Initial work presented here reports on the period 1926 to 1941.
Keywords: American Association for Adult Education; Journal of Adult Education; women contributors